Problems Faced by Special Teachers in Implementing Inclusive Education under Sarva Shiksha Abhiyan - Dubey, Varun Kumar; Pandey, Yogendra (JOURNAL OF INDIAN EDUCATION, 2012)
As free and compulsory elementary education for the children of age group 6 to 14 years become the fundamental right through inclusion of article 21A in part III of Indian Constitution, a recent initiative of Government of India to universalise elementary education has been taken as Sarva Shiksha Abhiyan (SSA). An endeavour has been made to implement the inclusive education through SSA. The responsibility of education of Children With Special Educational Needs (CWSENs) under SSA goes to special teachers appointed as Itinerant or Resource Teachers as well as regular counterpart, while the key persons to implement inclusive education under SSA are these special teachers. The present study carried out in Varanasi district of Uttar Pradesh incorporates 20 special teachers as sample and as a tool investigator’s made questionnaire based on six dimensions was used to analyse the data. Survey method and purposive sampling method was used to investigate the problems. Findings of the study reveals that special teachers face problems regarding non-cooperation of government officials which have the responsibility of inclusive education under SSA and financial problems were also reported by them. They also have fear of job insecurity and they found themselves under pressure due to over workload. All these problems revealed under investigation adversely affect the implementation of inclusive education under SSA.